Methodologic Considerations and Conclusions (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2013)
After the theoric seasons of the second middle of the Twenthieth century especially by the anglo-american Scholars and the beginning of the open area excavations enterprises in Italy thirty years ago, the concept of the therm “method” holds now a multiplicity of aspects one another connected; their theorical and practical applications make valuable the method universality but it depends on the characteristics of the archaeological site too. So Nora with its historical-archaeological stratification is an exemplary specimen from a lot of points of view like a precious source to draw stratigraphical sequences inside  large chronological oasis with very important monumental contexts. The universitary équipes were allowed to adopt a modern methodological practice, founded on technological resources, that leads to a perspective which contains the archaeology of architecture and the archaeology of the smallest clue compared together. The fast and careful editions of the field-works in the “Quaderni Norensi” Collection, enriched by an exhaustive documentary evidence, constitutes an indispensable contribution to the reconstruction of the ancient town and the best trial to test a research model “open-area” between équipes differently formed but in a scientific homogeneous climate.
Keywords: Nora; Quaderni Norensi; Method; Central Quarter; Field Archaeology; Allan Pierson Museum